2011
DOI: 10.1139/h11-073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-dose large neutral amino acid supplementation on exercise, motor skill, and mental performance in Australian Rules Football players

Abstract: This study investigated the effects of high-dose large neutral amino acid (LNAA) supplementation on attenuating fatigue-induced decrements in exercise and motor skill performance in Australian Rules Football (ARF) players. Fifteen subelite ARF players participated in 3 testing sessions separated by 7 days. Players completed an initial control trial involving a reactive motor skills test (RMST) and a reactive agility test (RAT) carried out before and after fatiguing exercise. In the subsequent experimental tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…In the AA trial, the significantly decreased plasma tryptophan/BCAA ratio would reduce cerebral serotonin synthesis and subsequently alleviate central fatigue (Gomez‐Merino et al., ). In agreement, previous studies have reported that BCAA supplementation could maintain cognitive functions (Hassmen et al., ) and the performance in reactive motor skills (Stepto et al., ), while reducing the feeling of fatigue (Blomstrand et al., ) during strenuous exercise. Furthermore, the AA and PB trials produced similar post‐match plasma NH 3 concentrations, indicating the absence of excess hyperammonemia from BCAA metabolism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the AA trial, the significantly decreased plasma tryptophan/BCAA ratio would reduce cerebral serotonin synthesis and subsequently alleviate central fatigue (Gomez‐Merino et al., ). In agreement, previous studies have reported that BCAA supplementation could maintain cognitive functions (Hassmen et al., ) and the performance in reactive motor skills (Stepto et al., ), while reducing the feeling of fatigue (Blomstrand et al., ) during strenuous exercise. Furthermore, the AA and PB trials produced similar post‐match plasma NH 3 concentrations, indicating the absence of excess hyperammonemia from BCAA metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…It has been hypothesized that BCAA could prevent exercise‐induced central fatigue by competing for the same transporter across blood–brain barrier with tryptophan (Blomstrand, ). Previous studies have reported that BCAA supplementation could maintain cognitive functions (Hassmen et al., ) and performance in reactive motor skills (Stepto et al., ), while reducing the feeling of fatigue (Blomstrand et al., ) during strenuous exercise. However, one disadvantage for BCAA supplementation is the excess hyperammonemia as the result of the increased metabolism of these amino acids during exercise (MacLean et al., ).…”
mentioning
confidence: 99%
“…Any modification to metabolites may affect exercise tolerance. Previous studies have shown that supplementation with amino acids can lead to changes in energy metabolites and physical performance [18,29-32]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, leucine/ protein ingestion reduced the overall perception of tiredness on the profile of a mood states questionnaire by 13% (20). When an amino acid formula high in branched-chain amino acids (BCAAs) was ingested 3 h before performance trials in Australian Rules Football players, playersÕ scores on an intricate reactive motor skills and agility performance test improved significantly (21). For the SPECOPS soldier, these results suggest that inclusion of amino acids/protein may confer benefits related to tasks requiring gross motor skills, as well as those requiring more specialized motor skills.…”
Section: Performance Benefits Of Protein Coingestion During Activitymentioning
confidence: 99%